2021
DOI: 10.1177/15353702211015620
|View full text |Cite
|
Sign up to set email alerts
|

Olaparib attenuates sepsis-induced acute multiple organ injury via ERK-mediated CD14 expression

Abstract: Sepsis is characterized by persistent systemic inflammation, which can cause multi-organ dysfunction. The poly polymerase-1 inhibitor olaparib possesses anti-inflammatory properties. This study aimed to assess the effects of olaparib (pre- and post-treatments) on sepsis, and to investigate whether it could suppress CD14 expression via the ERK pathway in polymicrobial sepsis and peritoneal macrophages models. Sepsis was induced by cecal ligation and puncture in C57BL/6 male mice. Fifty mice were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Liver injury scoring was performed as previously described 43 : inflammation, edema, haemorrhage and tissue necrosis, with scores of 0, 1, 2, 3 and 4 for each parameter as none, minimal, mild, moderate and severe, respectively.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…Liver injury scoring was performed as previously described 43 : inflammation, edema, haemorrhage and tissue necrosis, with scores of 0, 1, 2, 3 and 4 for each parameter as none, minimal, mild, moderate and severe, respectively.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“… 2017 ; Chen et al. 2021 ). The findings of current study indicated that the secretion of cTnI, CK, CK-MB, Cr, BUN, ALT, and AST induced by CLP treatment could be reversed by parenteral ω-3 PUFAs solutions treatment, suggesting the protective role of ω-3 PUFA solutions in sepsis induced multi-organ injury.…”
Section: Discussionmentioning
confidence: 99%